Ecotourism policy and planning (CABI, 2003)
This book provides an overview of the extent of international ecotourism policy. A key objective of the book is to highlight the importance of balancing social, ecological, and economic factors in the development of policy for the ecotourism industry. Thus sustainability issues are addressed from a variety of approaches at a range of levels. The book is divided into five main sections focusing on the theoretical considerations of ecotourism policy and planning (section 1) followed by case studies at a range of levels including regions (2), countries (3) and continents (4), ending with some brief conclusions (5). The book will be of significant interest to researchers, practitioners and policy makers in tourism, environment, geography and planning. It has 17 chapters and a subject index.